2016
DOI: 10.1080/01496395.2015.1131720
|View full text |Cite
|
Sign up to set email alerts
|

Study on adsorption of Cu(II)–Cr(VI) binary system by carbonized Eupatorium adenophorum

Abstract: We first report a mechanism study on the adsorption of Cu(II)-Cr(VI) binary mixture by a novel low-cost adsorbent, carbonized Eupatorium adenophorum. The influences by pH value, dosage, initial concentration, temperature, and adsorption time on its performance to absorb copper and chromium were investigated. The experimental data were fitted according to the Langmuir and Freundlich adsorption isotherm models, the pseudo-first-order kinetics, the pseudo-second-order kinetics, and the intra-particle diffusion mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…C1 presented a higher Qmax than other bioadsorbents reported in the literature (Chen et al, 2016;Dong et al, 2010). For example, Chen et al (2016) (Dong et al, 2010).…”
Section: Adsorption Of Cu(ii) and Oxyanions Of Cr(vi) On C1 As A Function Of Initial Solute Concentrationmentioning
confidence: 73%
See 2 more Smart Citations
“…C1 presented a higher Qmax than other bioadsorbents reported in the literature (Chen et al, 2016;Dong et al, 2010). For example, Chen et al (2016) (Dong et al, 2010).…”
Section: Adsorption Of Cu(ii) and Oxyanions Of Cr(vi) On C1 As A Function Of Initial Solute Concentrationmentioning
confidence: 73%
“…C1 presented a higher Qmax than other bioadsorbents reported in the literature (Chen et al, 2016;Dong et al, 2010). For example, Chen et al (2016) (Dong et al, 2010). In a previous study, Almeida et al (2016) reported the synthesis of an efficient adsorbent by quaternization of the amine group of chitosan and esterification of -OH groups with EDTA dianhydride.…”
Section: Adsorption Of Cu(ii) and Oxyanions Of Cr(vi) On C1 As A Function Of Initial Solute Concentrationmentioning
confidence: 91%
See 1 more Smart Citation
“…Ageratina adenophora , common name: Crofton weed), is now a widespread noxious invasive weed, which is spreading rapidly in China and causing substantial damage to the ecological environment currently ( Oelrichs et al., 1995 ; Sharma et al., 1998 ; Wan et al., 2010 ; Wan et al., 2010 , 2010 ; Wang and Wang, 2006 ; Wu et al., 2020 ; Yu et al., 2005 ; Zheng et al., 2009 ). Studies have shown that, in some metal mines where E. adenophorum had spread, it has been proven to be an efficient accumulator of lead (Pb), Zinc (Zn), and cadmium (Cd) ( Chen et al., 2014 , 2016 ; Li et al., 2016 ; Li and Zhang, 2008 ; Song et al., 2016 ; Wang et al., 2013 ; Wang and Zhang, 2008 ; Zu et al., 2005 ). These metals deposited in E. adenophorum may be transmitted and bio-accumulated in natural enemies, which will frequently exert significant negative effects on natural enemies, influencing its parasitic activity, for example, Procecidochares utilis Stone ( Wang et al., 2013 ; Ma et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%